The Position of Arbitration in Dispute Resolution of Islamic Financial Institutions - Adi Astiti, Ni Nyoman; Rahman, Ghozali; Ibtisamah, Siti Nur (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
Arbitration in Islamic law is known as the term tahkim which comes from Arabic. Arbitration in Islam has been recognized in the Al-Qur